Паліноморфологія видів секції Pseudolysimachium W.D.J. Koch роду Veronica L. (Scrophulariaceae) флори України - Цимбалюк, З.М. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2008)
Изучены пыльцевые зерна 12 видов секции Pseudolysimachium рода Veronica флоры Украины; у 9 видов пыльца описана впервые. Выделены и описаны 5 типов скульптуры поверхности экзины: гладкий, морщинистый, ямчатый, морщинисто-ямчатый и сетчатый. Установлено, что пыльцевые зерна изученных видов имеют сложный тип апертур: 3(4)-бороздно-оровый. Полученные данные свидетельствуют о филогенетическом единстве данной группы и ее отличии от других секций рода Veronica, которые характеризуются иным комплексом палиноморфологических признаков (3-бороздные пыльцевые зерна, струйчатая, струйчато-сетчатая, гранулярная, бугорчатая, палочковая и шипиковатая скульптура). Pollen grains of 12 species of Veronica sect. Pseudolysimachium were investigated, including 9 species for which no previous palynological data existed. Five types of sculpture of the exine surface have been identified and described: psilate, rugulate, foveate, rugulate-foveate, and reticulate. Pollen grains are characterized by morphologically complex 3(4)-colporate aperture types. The data obtained provide evidence in favor of the phylogenetic unity of this group and its distinction from other sections of the genus Veronica, which are characterized by different complexes of palynomorphological characters (3-colpate pollen grains, striate, striate-reticulate, granulate, tuberculate, retipilate and spinulose sculpture).